Opioids and Gabapentinoids Utilisation and Their Related-Mortality Trends in the United Kingdom Primary Care Setting, 2010–2019: A Cross-National, Population-Based Comparison Study - Kurdi, Amanj (Frontiers in Pharmacology, 2021)
Background There is growing concern over the increasing utilisation trends of opioids and gabapentinoids across but there is lack of data assessing and comparing the utilisation trends across the four UK countries. We assessed/compared opioids and gabapentinoids utilisation trends across the four UK countries then evaluated the correlation between their utilisation with related mortality. Method This repeated cross-national study used Prescription Cost Analysis (PCA) datasets (2010-2019). Opioids and gabapentinoids utilisation were measured using number of items dispensed/1000 inhabitants and defined daily doses (DDDs)/1000 inhabitant/day. Number of Opioids and gabapentinoids-related mortality were extracted from the UK Office for National Statistics (2010-2018). Data were analysed using descriptive statistics including linear trend analysis; correlation between the Opioids and gabapentinoids utilisation and their related mortality using Pearson correlation coefficient. Results The results illustrated an overall significant increasing trend in the utilisation of opioids (12.5%-14%) and gabapentinoids (205%-207%) with substantial variations among the four UK countries. For opioids, Scotland had the highest level of number of items dispensed/1000 inhabitant (156.6% higher compared to the lowest level in England), whereas in terms of DDD/1000 inhabitant/day, NI had the highest level. Utilisation trends increased significantly across the four countries ranging from 7.7% in Scotland to 20.5% in NI (p<0.001). Similarly, for gabapentinoids, there were significant increasing trends ranging from 126.5%-114.9% in NI to 285.8%-299.6% in Wales (p<0.001) for number of items/1000 inhabitants and DDD/1000 inhabitant/day, respectively. Although the utilisation trends levelled off after 2016, this was not translated into comparable reduction in opioids and gabapentinoids-related mortality as the latter continued to increase with the highest level in Scotland (3.5 times more deaths in 2018 compared to England- 280.1 vs. 79.3 deaths/million inhabitants). There were significant moderate-strong positive correlations between opioids and gabapentinoids utilisation trends and their related mortality. Conclusion The utilisation trends of opioids and gabapentinoids have increased significantly with substantial variations among the four UK countries. This coincided with significant increase in their related mortality. Our findings support the call for immediate actions including radical changes in official UK policies on drug use and effective strategies to promote best clinical practice in opioids and gabapentinoids prescribing